If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 25x = 2 + 0x + 12 Anything times zero is zero. 3 + 25x = 2 + 0x + 12 Combine like terms: 2 + 0 = 2 3 + 25x = 2 + 12 Combine like terms: 2 + 12 = 14 3 + 25x = 14 Solving 3 + 25x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 25x = 14 + -3 Combine like terms: 3 + -3 = 0 0 + 25x = 14 + -3 25x = 14 + -3 Combine like terms: 14 + -3 = 11 25x = 11 Divide each side by '25'. x = 0.44 Simplifying x = 0.44
| 34+(25x)+(35x)=93 | | 34+(25x)+(35x)=94 | | (1+i)*z*z+2iz-1=0 | | 34+(25x)+(35x)=90 | | 34(25x)(35x)=90 | | 2z+20z=o | | 55-3x=6-10x | | 4x+15=-5x-12 | | 2x-5+57=3x+9 | | 5y+6-9y= | | 9x+17=4x+42 | | 13=4x-15 | | -6+(-1-b)=19 | | m^2+3=4 | | A=-3a-16 | | 3r^2=-45 | | cos(c)+3*sin(c)=2 | | x=22y+39x | | 4x-5=6x+23 | | Log[2](3x+8)=5 | | 3x-2=-5x-6 | | -h^2+15h+50=0 | | -61= | | Y^2=5Y+50 | | 89=28-r | | 36=-3(-9-3z) | | 33x+117=14.5x | | 6x^3-4x-16x=0 | | 89=21-r | | 12=-8p+11+9p | | 1.5x+10=2x+20 | | 1216=(x*2140)/(7443,8*0,1) |